Propagating the Israelite way of life in the book of Tobit and in Jubilees: Tobit and Noah as exemplary characters - Antin, Katri (Journal for the study of the pseudepigrapha, 2023)
This study explores the fluidity of beliefs and practices depicted distinctively Israelite in the Book of Tobit and Jubilees. The comparison between Tobit’s and Noah’s characters demonstrates that their exemplarity is depicted similarly by using the two-way metaphor, but the beliefs that these characters propagate are very different. Drawing on the social identity approach, this article shows that the authors of the Book of Tobit and Jubilees compare different groups that affect which beliefs and practices characterize the ideal way of life: Different features are presented as exemplary when ethnic groups are compared to one another as opposed to when different tribes/families are compared. Similarly, the exemplary characteristics are different when common ancestry is defining for Israelite identity in comparison to when covenantal obedience is defining. The comparative context does not change only between the Book of Tobit and Jubilees but also within each book. The shift in the comparative context offers one explanation for the literary seams in the Book of Tobit.